Does the Consumption of Green Tea Reduce the Risk of Lung Cancer among Smokers?. Issue 1 (2007) - Liang, Wenbin; Binns, Colin W.; Jian, Le; Lee, Andy H.
Abstract : Experimental and epidemiological studies were reviewed to assess whether the consumption of green tea could reduce the risk of lung cancer in smokers. Articles published since 1990 were located by searching electronic databases PubMed, Ovid and Science Direct, using keywords 'lung cancer', 'tea' and 'smoking' without any restriction on language. After relevant articles had been located, further papers were obtained from their reference lists. Evidence from experimental studies ( in vitro animal and human trials) suggested that regular intake of green tea may be protective against tobacco carcinogens. However, the mechanism behind the protective effect is only partly understood. In most of the epidemiological studies reviewed, the green tea exposure was within 5 years of the interview or follow-up, which would coincide with the induction period and latent period of lung cancer. Longer term studies are thus needed to further quantify the cancer risk. There is some evidence suggesting regular intake of green tea at high level (>3 cups per day) may reduce the risk of smokers developing lung cancer. Improvement in measuring green tea intake is required in order to confirm the evidence from epidemiological studies.